MAX-MIN EDGE MAGIC AND ANTIMAGIC LABELING - Jayapriya, J.; Thirusangu, K. (European Scientific Journal, ESJ, 2013)
In this paper we introduce a new type of edge magic and antimagic labeling and study the same for various classes of graphs.